Sistem Pemerintahan Desa Di Kabupaten Buru Selatan - Salim, Rivaldy; Salmon, Hendrik; Bakarbessy, Andress Demy (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The customary law community unit on Buru Island is divided into several areas centered on a certain area. Where, the leader at the Regenschaap level is called the title Jou or Raja as in Central Maluku. However, in practice there is also a village government system that includes the village head and village government staff as well as the Village Consultative Body.Purposes of the Research: To study and find out whether the village government system in the southern hunting district is still based on customary law values or not.Methods of the Research: The type of research used is research that will be used in the research is normative legal research.Results of the Research: The village government system in the southern buru district still has traditional values called the Fena which consists of (marga-marga) uniting themselves in an alliance, and has the highest leader called Mat Gugul. The village government system in South Buru Regency with construction combining the functions of self-governing community (customary village) with local self-government (village), where there is a Fena led by a village head, who is accompanied by a Saniri institution consisting of Geb. 'ha (soa) and soa represent the clan which is also known as Fena. In addition, there is also the Regenschaap government which can also be referred to as the leader in the territory led by Jou or Raja. A Regenschaap oversees several villages.